Circulating plasma and exosome levels of the miR-320 family as a non-invasive biomarker for methamphetamine use disorder - Xu, Wenjin; Hong, Qingxiao; Zhou, Yun; Chen, Xiaoyu; Li, Longhui; Wang, Majie; Chen, Weisheng; Xie, Xiaohu; Zhuang, Dingding; Lai, Miaojun; Zhou, Wenhua; Liu, Huifen (Frontiers in Psychiatry, 2023)
The neurobiological mechanism of methamphetamine(MA) use disorder was still unclear, and no specific biomarkers exist for clinical diagnosis and treatment. Recent studies have demonstrated that microRNAs (miRNAs) are involved in the pathological process of MA addiction. The purpose of this study was to identify novel miRNAs as biomarkers for the diagnosis of MA user disorder. First, members of the miR-320 family, including miR-320a-3p, miR-320b, and miR-320c, were selected and analyzed in the circulating plasma and exosome by microarray and sequencing. Secondly, miR-320 in plasma was quantified by real-time quantitative reverse transcription polymerase chain reaction(RT-qPCR) in eighty-two patients exhibiting MA use disorder and fifty age-gender-matched healthy controls. We also analyzed miR-320 expression in the exosome of thirty-nine patients exhibiting MA use disorder and twenty-one age-matched controls. Subsequently, diagnostic power was evaluated using the area under the curve (AUC) of the receiver operating characteristic (ROC) curve. The results showed that miR-320 was significantly increased in MA use disorder plasma and exosomes compared with controls. The AUC of the ROC curves of miR-320 in MA use disorder plasma and exosome were 0.751 and 0.962, respectively. The sensitivities of miR-320 in MA use disorder plasma and exosome were 0.900 and 0.846, respectively, whereas the specificities of miR-320 were 0.537 and 0.952, respectively. Among the increases in miR-320 in MA use disorders patients, the increase in miR-320 in the plasma was positively correlated with smoking, age of onset, and daily use. Target prediction with miR-320 identified pathways implicated in MA addiction, including cardiovascular disease, synaptic plasticity, and neuroinflammation. Together, our findings indicated that plasma and exosome associated miR-320 might be used as a potential blood-based biomarker for diagnosing MA use disorder.